Education without Debt : Giving Back and Paying It Forward - MacDonald, Scott (Book collections on Project MUSE., 2021)
-Examines the student debt crisis in the US, and proposes possible solutions. -Showcases first-person accounts of those impacted by student debt. -Author, Scott MacDonald, is a noted businessman and educational philanthropist.